Shaping triple-conducting semiconductor BaCo0.4Fe0.4Zr0.1Y0.1O3-δ into an electrolyte for low-temperature solid oxide fuel cells - Chen Xia (Nature Portfolio, 2019)
Solid oxide fuel cells enable efficient electricity generation at high temperatures. Here the authors incorporate a mixed ion-electron semiconductor into another semiconductor to form a p-n junction to suppress electron conduction and enhance ion conduction, leading to a low-temperature electrolyte.